Expert Evaluation of Potential Points of Economic Growth in the Regions of Russia and the Conditions of their Development - A. V. Tihonov; V. S. Bogdanov; A. A. Pochestnev (Модернизация, инновация, развитие)
Purpose: the main purpose of this article is to identify « growth points» of economic growth in the regions, determine their type, and assess the conditions for their development. Methods: the main feature of this study is to obtain an expert assessment of the qualitative aspects of regional development. The main source of empirical data was an online survey conducted by the authors in 2016. Results: the study identified potential «growth points» in five regions of the Russian Federation and determined their nature according to the idea of modernizing the socio-economic environment. The selected points allow to develop the potential of the region horizontally. However, there are certain problems that hinder this development and they have been identified. Conclusions and Relevance: at the moment, the identified «growth points» can not be classified as information or intellectual, but in all regions there is the possibility of activating such industries. The «growth points» allocated by experts are still potential, because their technical, technological and innovative components have medium level of development. «Growth points» in the Republic of Sakha and the Nizhny Novgorod region have a greater modernization activity. Such expertise can be used by local authorities to adjust development vectors and strategies. It can also be an element of monitoring the socioeconomic development of regions.